On (N+l) - stage planar photonic switches - M. Suliman, Fakher Eldin; Seman, Kamaruzzaman; Mohammad, Abu Bakar (2000)
N-stage planar architectures are attractive for pbotonic switches made of directional couplers because they have no crossovers. However, compared to crossbar switches, they have fewer number of crosspoints and therefore are rearrangeably nonblocking. To have a small number of crosspoints and at the same time improve the blocking probability, the (N+1)-stage planar switch is proposed in this paper. The development of this switch from the former one will be explained. The tow switches will be compared to address their performance, advantages, and limitations.